THE INFLUENCE OF ANDROID-BASED MUSIC MEDIA AND CONVENTIONAL MUSICAL INSTRUMENTS AND LEARNING MOTIVATION ON THE RESULTS OF JUNIOR HIGH SCHOOL STUDENTS' MUSIC ENSEMBLE - Trisia Santi Parlina; Rufi'i Rufi'i; Reza Rachmadtullah (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
This study aims to analyze the influence of learning media (Android-based music applications and conventional musical instruments) and learning motivation on the learning outcomes of junior high school students' music ensembles. The study used a quantitative approach with a 2×2 factorial quasi-experimental design on 60 students grouped by media type and learning motivation level. The research instruments included a learning outcome test and a motivation questionnaire (Cronbach's Alpha 0.85–0.87). Data analysis included normality, homogeneity, and two-way ANOVA tests. The results showed a significant increase between pretest and posttest scores (t = 12.84; p = 0.000). The ANOVA test revealed that learning media had a significant effect on learning outcomes (F(1,56) = 14.62; p = 0.000; η² = 0.21). Learning motivation also had a significant effect (F(1,56) = 32.45; p = 0.000; η² = 0.37). In addition, there was a significant interaction between media and motivation (F(1,56) = 4.18; p = 0.046; η² = 0.07). Highly motivated students using the Android application obtained the highest average score (Mean = 88.75), while lowly motivated students using conventional media showed the lowest score (Mean = 64.38). This finding confirms that Android-based music applications can significantly improve the effectiveness of music ensemble learning, especially for students with high motivation. The integration of digital technology is recommended as an alternative learning strategy that is interactive, flexible, and supports the improvement of students' musical performance.